2021
DOI: 10.1080/07391102.2021.1921032
|View full text |Cite
|
Sign up to set email alerts
|

Marine algal antagonists targeting 3CL protease and spike glycoprotein of SARS-CoV-2: a computational approach for anti-COVID-19 drug discovery

Abstract: The COVID-19 pandemic has severely destructed human life worldwide, with no suitable treatment until now. SARS-CoV-2 virus is unprecedented, resistance against number of therapeutics and spreading rapidly with high mortality, which warrants the need to discover new effective drugs to combat this situation. This current study is undertaken to explore the antiviral potential of marine algal compounds to inhibit the viral entry and its multiplication using computational analysis. Among the proven drug discovery t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 72 publications
0
17
0
Order By: Relevance
“…Our top-ranked compound of eugeniin (−9.8 kcal/mol), syzyginin B (−10.4 kcal/mol), eugenol (−7.3 kcal/mol), and casuarictin (−12.2 kcal/mol) has shown higher binding affinity than the commercially available drugs such as remdesivir (−6 kcal/mol), liponavir (−4 kcal/mol), tamiflu (−5.72 kcal/mol), plaquenil (−5.59 kcal/mol), and mycophenolic (−6.02 kcal/mol) ( Arunkumar et al, 2021 ; Khater and Nassar, 2021 ). Eugenol is extracted from cloves, is abundantly present in the clove oil, is used for antispasmodic treatment, and acts as a carminative to treat gastrointestinal disorders.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our top-ranked compound of eugeniin (−9.8 kcal/mol), syzyginin B (−10.4 kcal/mol), eugenol (−7.3 kcal/mol), and casuarictin (−12.2 kcal/mol) has shown higher binding affinity than the commercially available drugs such as remdesivir (−6 kcal/mol), liponavir (−4 kcal/mol), tamiflu (−5.72 kcal/mol), plaquenil (−5.59 kcal/mol), and mycophenolic (−6.02 kcal/mol) ( Arunkumar et al, 2021 ; Khater and Nassar, 2021 ). Eugenol is extracted from cloves, is abundantly present in the clove oil, is used for antispasmodic treatment, and acts as a carminative to treat gastrointestinal disorders.…”
Section: Resultsmentioning
confidence: 99%
“…The structure was subjected to protein preparation using autodock tools, a graphical user interface program, which was exploited for the preparation, running, and analyzing the docking simulations. Water molecules, ligand groups (inhibitor), and other nonspecific molecules were removed, polar hydrogen was added with the merging nonpolar hydrogens, and partial charges were assigned ( Arunkumar et al, 2021 ). The grids are placed in the region that possesses the nature of an active site since grids direct the ligand toward the binding site ( Forli et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Carrageenan had been exploited with antimicrobial, antiviral, and anticancer activity. The current research observed a significant interaction of the carrageenan with multiple targets resulting majorly around −7 to −6 Kcal/mol binding score [ 28 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Computational methods such as molecular docking have played a critical role in rationalizing the road to drug discovery in order to overcome these obstacles. A molecular docking feature becomes a promising pharmaceutical research tool for screening candidates from drug libraries effectively [ 28 ]. In such studies, the ultimate goal was to find effective therapeutics for the carrageenan molecule extracted from marine algae.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these barriers, computational approaches such as molecular docking have played a significant role in streamlining the road to drug development. The use of molecular docking technology in drug research is currently a valuable method for quickly screening candidates from drug libraries [3]. B. diffusa is commonly known as red spiderling or common hogweed.…”
Section: Introductionmentioning
confidence: 99%